2017
DOI: 10.1145/3134437
|View full text |Cite
|
Sign up to set email alerts
|

Cache Exclusivity and Sharing

Abstract: A problem on multicore systems is cache sharing, where the cache occupancy of a program depends on the cache usage of peer programs. Exclusive cache hierarchy as used on AMD processors is an effective solution to allow processor cores to have a large private cache while still benefitting from shared cache. The shared cache stores the "victims" (i.e., data evicted from private caches). The performance depends on how victims of co-run programs interact in shared cache.This article presents a new metric called th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…showed that footprint enables more general models of cache associativity, as well as modelling the sub-block cache, and these models can be used together. Furthermore, the effect of multi-level caches, i.e., the effect of cache "filtering," can be modeled using an extension of the footprint called the 'victim footprint" by Ye et al (2017) and "average eviction time" (AET) by Hu et al (2018).…”
Section: Composability and Cache Sharingmentioning
confidence: 99%
“…showed that footprint enables more general models of cache associativity, as well as modelling the sub-block cache, and these models can be used together. Furthermore, the effect of multi-level caches, i.e., the effect of cache "filtering," can be modeled using an extension of the footprint called the 'victim footprint" by Ye et al (2017) and "average eviction time" (AET) by Hu et al (2018).…”
Section: Composability and Cache Sharingmentioning
confidence: 99%